Association Between Healthy Dietary Patterns and Markers of Oxidative Stress. (14th June 2022) - Crawford, Brittany; Sandler, Dale; Nichols, Hazel; Milne, Ginger; Steck, Susan; Park, Yong-Moon
Abstract: Objectives: Oxidative stress is involved in chronic disease etiology and the aging process and is related to antioxidant intake. However, less is known about the relationship between dietary patterns and markers of oxidative stress. We assessed cross-sectionally the association between healthy dietary patterns [alternate Mediterranean diet (aMED), Dietary Approaches to Stop Hypertension (DASH), alternative Healthy Eating Index (aHEI), and Healthy Eating Index 2015 (HEI-2015)] and urinary F2 -isoprostanes (8-iso-PGF2α and 8-iso-PGF2α-M), which are established biomarkers of oxidative stress. Methods: Data were obtained from 844 premenopausal and 454 postmenopausal women participating in the Sister Study who had urinary samples analyzed for F2 -isoprostanes. Responses from a 110-item validated food frequency questionnaire (FFQ) at baseline were used to calculate dietary pattern scores. Concentrations of 8-iso-PGF2α and its metabolite (8-iso-PGF2α-M) were measured by GC/MS for samples from premenopausal women and LC/MS for samples from postmenopausal women. Multivariable linear regression models were used to estimate associations between aMED, DASH, aHEI, and HEI-2015 and urinary F2 -isoprostanes among pre-menopausal and post-menopausal women separately. Results: Among premenopausal women, we observed significant inverse associations between the four dietary indices and mean 8-iso-PGF2α (aMED βQ4vsQ1 : −0.15, 95% CI: −0.25, −0.05; DASH βQ4vsQ1 : −0.15, 95% CI: −0.25, −0.25; aHEI βQ4vsQ1 : −0.15, 95% CI: −0.25, −0.05; HEI-2015 βQ4vsQ1 : −0.17, 95% CI: −0.27, −0.07). These associations were modified by age, education, income, and BMI, though there was no evidence of statistical interaction. In a sensitivity analysis, estimates did not substantially differ by the presence or absence of chronic disease. Among postmenopausal women, aHEI was associated with mean 8-iso-PGF2α and 8-iso-PGF2α-M (β8-iso-PGF2α : −0.003, 95% CI: −0.01, −0.005, β8-iso-PGF2α-M : −0.003, 95% CI: −0.01, −0.005). No other significant findings were observed among postmenopausal women. Conclusions: Healthy dietary patterns may be associated with reduced oxidative stress, particularly among premenopausal women. Funding Sources: National Institute of Environmental Health Sciences, NIH Office of Dietary Supplements, Avon Foundation, T32 from NIH-NIGMS.